Origami for little hands : more than 30 animal foldings, toys, and decorations - Hodoshima, Sayaka (Happy Fox Books, 2023)
"A super fun origami book for kids, this book is perfect for young minds and little hands! From a penguin and a crab to a boat, a butterfly, and so much more, the paper craft projects featured in this must-have origami book are adorable as they are fun to make. Kids ages 4-7 will be entertained for hours as they learn how to origami over 30 awesome paper crafts of sea animals, farm animals, hearts, objects, and more! Featuring step-by-step instructions, easy-to-follow visual guides, information on paper, and a helpful abbreviation chart, Origami for Little Hands is a fun and exciting craft guide that makes for the great introduction to making amazing paper crafts with just a few folds!"--